(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The integration of Science, Technology, Engineering, Arts, and Mathematics (STEAM) education with English language teaching (ELT) represents a significant pedagogical shift, particularly in contexts where traditional, test-based approaches have limited student engagement and application skills. This interdisciplinary approach aims to cultivate innovative talents with multidimensional literacy by fostering creative, critical, and imaginative thinking. This article explores the application of STEAM technologies in English language teaching, structured according to the Introduction, Methods, Results, and Discussion, which is a standard for scientific writing in STEM disciplines.